Pengembangan Materi Teks Fabel Berbasis Media Scribe Sparkol di Kelas VII SMP Negeri 1 Pantai Labu - Irawan, Sumba; Umar, Azhar (Medan Resource Center, 2023)
This research aims to develop fable text materials for seventh-grade students using the Scribe Sparkol media and assess the product's feasibility. Following the Borg and Gall procedure, the study involved 38 samples, utilizing a Likert Scale for needs and problem analysis, product validation, teacher assessments, student responses, and learning implementation observations. The results indicate the product,